The political economy of policy coordination : international adjustment since 1945 - Webb, Michael C. (Cornell studies in political economy., 1995)
Michael C. Webb explores a central question about postwar economic history: how has the growth of international markets affected the coordination of economic policy among nations? His analysis overturns the popular assumption that policy coordination has eroded as American hegemony has receded. Instead, he argues that the growing mobility of capital forced governments to abandon the strategies they had used in the 1950s and 1960s to insulate monetary and fiscal policies from international influences, and to move toward more direct coordination of central economic strategies.